The Influence of the Anak Indonesia Hebat Physical Fitness Gymnastics on Increasing the Interest of Grade VII Students in Participating in Morning Gymnastics Activities at SMP Negeri 1 Lawe Sigala-gala - Ladipin, Ladipin; Reviza, Liza; Handayani, Fitri; Nadeak, Renia Margaretha (Association of Islamic Education Managers (Permapendis) Indonesia, North Sumatra Province, 2025)
The purpose of this study is to determine the effect of Senam Kebugaran Jasmani (SKJ) Anak Indonesia Hebat exercises on increasing the interest of seventh-grade students in participating in morning exercise activities at SMP Negeri 1 Lawe Sigala-gala. The study was conducted on the school field of SMP Negeri 1 Lawe Sigala-gala using a quantitative method through observations and a physical fitness test to measure students’ interest levels. The research subjects were all 30 seventh-grade students, selected using the total sampling technique, in which the entire population was used as the sample. The average pre-test score was 42, and after the implementation of the SKJ Anak Indonesia Hebat program, the post-test average score increased to 78. The data analysis results showed a significant increase in students' interest in participating in morning exercises after receiving the SKJ Anak Indonesia Hebat training. This increase is evident as many students showed enthusiasm for the program due to its physical and mental benefits. Moreover, the program is accompanied by cheerful music, easy-to-follow movements, and promotes positive values such as discipline, cooperation, and joy. This study concludes that the Senam Kebugaran Jasmani Anak Indonesia Hebat training is effective in enhancing students’ interest in participating in morning exercise activities at school.